Are the Largest Banks Valued More Highly? - Minton, Bernadette A; Stulz, René M; Taboada, Alvaro G (Review of Financial Studies, 2019)
Some argue too-big-to-fail (TBTF) status increases the value of the largest banks. In contrast, we find that the value of the largest banks is negatively related to asset size in normal times, but much less so during the crisis. Further, shareholders lose when large banks cross a TBTF threshold through acquisitions. The negative relation between bank value and bank size for the largest banks cannot be explained by differences in ROA, ROE, equity volatility, tail risk, distress risk, or equity discount rates, but it can be partly explained by the market’s discounting of trading activities. Received December 20, 2017; editorial decision November 14, 2018 by Editor Itay Goldstein.